Usefulness of the modified asthma predictive index to predict the development of bronchial asthma in children - Saniz Diaz, Lisseth (2022)
Objective: To determine the usefulness of the modified asthma predictive index (mAPI) for the early detection of children diagnosed with bronchial asthma. Material y methods: Descriptive-cross-sectional study where 162 children from 5 to 16 years old, who belong to the Asthma program of Hospital III Yanahuara in Arequipa, were evaluated. His parents retrospectively answered an asthma predictive questionnaire consisting of 3 major criteria and 4 minor criteria. Probable asthma was considered if the child had recurrent wheezing, in addition to 1 major criterion and/or 2 positive minor criteria. Results: 85.8 % of the children began their disease before 4 years of age. When applying the mAPI retrospectively, it is observed that 76.5 % of childhood asthma could have been detected early (before the age of 5), with a higher positive score in males (81.2 %) and in children with moderate asthma severity (85.3 %). Conclusions: The mAPI is a simple and very easy-to-apply tool that allows early detection of the possibility of developing bronchial asthma in a young child (less than 5 years old) who presents recurrent wheezing in the last 12 months. Its routine use is recommended in pediatric consultation.